The interrelationship between childhood emotional abuse and aggressive behavior in the Chinese adolescent population: a network perspective - Yuhao Wang; Yuxuan Liu; Susu Tian; Xinyi Hu; Jiayi Tian; Yingxue Wang; Yihan Wang; Chunxia Miao; Wei Wang (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Numerous studies have found a strong correlation between emotional abuse in childhood and aggressive behavior in adolescents, especially among rural youth. However, the complex relationship between the different sub-dimensions of aggression and emotional abuse is unclear. This study aimed to explore the association between emotional abuse and different dimensions of aggressive behavior in rural adolescents using network analysis. Methods The participants in this study came from multiple middle schools and a total of 1797 adolescents were included in the study. Questionnaires were self-reported using the CTQ-SF (Childhood Trauma Questionnaire-Short Form) scale and Buss and Warren aggression questionnaire. A network analysis was performed. Results The network analysis revealed that hostility and anger were the most central dimensions of aggression, with " Sometimes I feel like people are laughing at me behind my back " and " I have a hard time controlling my temper " being the most influential nodes. Emotional abuse symptoms, particularly “Someone in my family has said insulting or sad things to me,” served as critical bridge symptoms, linking emotional abuse to aggressive behavior. Gender differences were significant, with males exhibiting stronger associations between emotional abuse and physical aggression, while females showed stronger links between emotional abuse and internalizing symptoms like hostility and anger. Conclusion This study highlights the central role of hostility and anger in the relationship between emotional abuse and aggressive behavior among rural adolescents. Poor family relationships, particularly insulting or demeaning remarks from family members, were identified as key bridge symptoms that exacerbate aggressive tendencies. Gender-specific patterns suggest that interventions should be tailored to address physical aggression in males and internalizing symptoms in females.